2001
DOI: 10.1051/0004-6361:20011286
|View full text |Cite
|
Sign up to set email alerts
|

Gravitationally lensed high redshift galaxies in the field of 1E0657-56

Abstract: Abstract. We present images and long-slit spectra obtained with FORS1 at UT1 of the VLT centered on the gravitational arc of the galaxy cluster 1E0657-56 (z = 0.296). The cluster is one of the hottest, most massive clusters known so far and acts as a powerful gravitational telescope, amplifying the flux of background sources by up to a factor of 20. We present photometric results together with the spectra of the gravitational arc (z = 3.24) and four additional amplified high redshift objects (z = 2.34 to 3.08)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 27 publications
4
54
0
Order By: Relevance
“…'I\1cker, Tananbaum, & Remillard (1995 did CCD imaging of the field and discovered the cluster as well as a 12" luminous arc. Mehlert, et al (2001) spectroscopically confirmed the object as an LBG.…”
Section: The Bullet Clustermentioning
confidence: 78%
See 3 more Smart Citations
“…'I\1cker, Tananbaum, & Remillard (1995 did CCD imaging of the field and discovered the cluster as well as a 12" luminous arc. Mehlert, et al (2001) spectroscopically confirmed the object as an LBG.…”
Section: The Bullet Clustermentioning
confidence: 78%
“…in tlw field of lE 0657-56, colloquially known as the Bullet Cluster. Mehlert, et al (2001) spectroscopically confirmed it as an LBG. The Bullet Cluster is actually at least two clusters in the process of merging and is one of the hottest X-ray clusters known (Tucker, et al 1998).…”
Section: The Bullet Clustermentioning
confidence: 80%
See 2 more Smart Citations
“…In the following section, we illustrate a method to help in the robust identification and/or deblending of the Herschel sources. Figure 1 shows thumbnails in several bands of two interesting sources detected by Herschel in the Bullet cluster field: the southern tip of the arc at z = 3.24 described in Mehlert et al (2001), and a sub-mm galaxy detected by LABOCA (source #10 in Johansson et al 2010). With these two examples, we demonstrate that the use of IRAC and MIPS data helps to correctly identify the Herschel sources with optical/NIR counterparts.…”
Section: Data and Catalogsmentioning
confidence: 87%